Analyse De La Diversité Floristique De La Forêt Classée D’agbo I (Côte d’Ivoire) - Estelle, N’guessan Anny; N’Dja, Justin Kassi (European Scientific Journal, ESJ, 2018)
This study was carried out in the Agbo I classified forest (6 ° 24 ’- 6 ° 41’ N, 4 ° 50 ’- 4 ° 09’ W), which covers 15,575 ha. It contributes to a better knowledge of the dense semi-deciduous moist forest of Nesogordonia papaverifera (A. Chev.) Cap. (Malvaceae) and Khayaivorensis A. Chev. (Meliaceae). The surface surveys coupled with the itinerant inventories made it possible to have an inventory of 686 species, which are divided into 428 genera and 101 families. The most abundant families are Fabaceae, Rubiaceae, Malvaceae, Apocynaceae, and Euphorbiaceae. Out of these species, 84.11% are phanerophytes and 3.50% are hemicryptophytes. In conclusion, this study improves the knowledge which is based on the composition, structure, and diversity of the woody vegetation of the Agbo I forest. The results show that the species richness of the Agbo I classified forest is important. However, this floristic richness of the Agbo I listed forest is sufficient to justify its protection and sustainable management for the conservation of biodiversity in Côte d’Ivoire.